Ultrasound evaluation of normal orbital preseptal thickness - Shrestha, A; Shrestha, S; Koirala, P; Pun, B (Nepalese Journal of Ophthalmology, 2017)
Introduction: Orbital preseptal thickness is an important parameter not only in diagnosis of orbital cellulitis but also in recent classification and management of dark eye circle (DEC). Objective: The aim of this study was to evaluate normal preseptal thickness and collect baseline data in normal skin in a given population with no orbital pathology. Materials & method: Ultrasound was performed on 42 patients (23 females and 19 males) with clinically normal eyes and orbits for evaluation of normal orbital preseptal thickness. The age ranged between 15 to 35 years with a mean age of 24.9 years. Results: Our study concluded that normal preseptal thickness ranged from 2.1 mm to 5.5 mm. Mean preseptal thickness for both sides was 3.9 mm. Conclusion: Ultrasound can be used as quick, reliable and cost–effective modality for evaluation of orbital preseptal thickness.